Adsorption of Selected Pharmaceutical Compounds onto Activated Carbon in Dilute Aqueous Solutions Exemplified by Acetaminophen, Diclofenac, and Sulfamethoxazole - E.-E. Chang; Jan-Chi Wan; Hyunook Kim; Chung-Huei Liang; Yung-Dun Dai; Pen-Chi Chiang (The Scientific World Journal)
The adsorption of three pharmaceuticals, namely, acetaminophen, diclofenac, and sulfamethoxazole onto granular activated carbon (GAC), was investigated. To study competitive adsorption, both dynamic and steady-state adsorption experiments were conducted by careful selection of pharmaceuticals with various affinities and molecular size. The effective diffusion coefficient of the adsorbate was increased with decease in particle size of GAC. The adsorption affinity represented as Langmuir was consistent with the ranking of the octanol-water partition coefficient, Kow. The adsorption behavior in binary or tertiary systems could be described by competition adsorption. In the binary system adsorption replacement occurred, under which the adsorbate with the smaller Kow was replaced by the one with larger Kow. Results also indicated that portion of the micropores could be occupied only by the small target compound, but not the larger adsorbates. In multiple-component systems the competition adsorption might significantly be affected by the macropores and less by the meso- or micropores.